2023
DOI: 10.3390/life13101967
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Brain-Derived Neurotrophic Factor (BDNF) in Depression and Cardiovascular Disease: A Systematic Review

Massimo Fioranelli,
Maria Grazia Roccia,
Bianca Przybylek
et al.

Abstract: Background: Several studies have been conducted to prove the bidirectional relationship between cardiovascular disease (CVD) and depression. These two major illnesses share several common risk factors such that the development of either condition may increase the risk of the occurrence of the other. Brain-derived neurotrophic factor (BDNF) has been suggested as a reliable biomarker for depression and a strong predictor of CVD because it plays an important role in neuron survival and growth, serves as a neurotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Likewise, as previously described, numerous studies have demonstrated that chronic stress can lead to reduced BDNF [13,62,63] and it is well known that BDNF is a neurotrophin considered as a biomarker of cognitive function [77][78][79] due to being essential for controlling synaptic plasticity and promoting dopaminergic neuron survival [80], also it is considered an important regulator of synaptic transmission and LTP in the hippocampus and in other brain regions and are involved in hippocampal neurogenesis [81].…”
Section: Plos Onementioning
confidence: 97%
“…Likewise, as previously described, numerous studies have demonstrated that chronic stress can lead to reduced BDNF [13,62,63] and it is well known that BDNF is a neurotrophin considered as a biomarker of cognitive function [77][78][79] due to being essential for controlling synaptic plasticity and promoting dopaminergic neuron survival [80], also it is considered an important regulator of synaptic transmission and LTP in the hippocampus and in other brain regions and are involved in hippocampal neurogenesis [81].…”
Section: Plos Onementioning
confidence: 97%
“…In stroke patients, BDNF release has been reported as a positive prognostic factor for patients poststroke recovery so that increasing BDNF levels are associated with faster and stronger recovery, while low levels of BDNF are associated with high stroke risk and poor recovery [46]. Okada et al (2012) demonstrated that the deletion of BDNF or disruption of TrkB in the heart leads to worsening of cardiac dysfunction after myocardial infarction [23].…”
Section: Introductionmentioning
confidence: 99%